Medicinal Plants for Viral Respiratory Diseases: A Systematic Review on Persian Medicine. (10th February 2023) - Hajimonfarednejad, Mahdie; Ostovar, Mohadeseh; Hasheminasab, Fatemeh Sadat; Shariati, Mohammad Ali; Thiruvengadam, Muthu; Raee, Mohammad Javad; Hashempur, Mohammad Hashem
Abstract : Introduction . Many medicinal plants have been introduced in Persian medicine references for various respiratory disorders. Considering the growing interest in herbal medicines, this review aimed to introduce medicinal herbs recommended by Persian Medicine (PM) references for respiratory diseases and to discuss their activity against respiratory viruses. Methods . The medicinal plants recommended for respiratory disorders were extracted from the main PM textbooks. Subsequently, their activity against respiratory viruses was systematically investigated via queries of scientific databases. Results . Searching PM references for medicinal plants used in the management of respiratory disorders yielded 45 results. Of them, 18 possess antiviral activity against respiratory viruses. There were 29 in vitro studies (including studies on human cell lines) and 5 in vivo studies. Conclusion . This research demonstrated that many of the medicinal plants mentioned for the respiratory diseases in PM have considerable activity against respiratory viruses. However, human studies regarding the reported medicinal plants are scarce.